The trade in papers marked with non-Latin characters : documents and history. - Regourd, Anne (Islamic manuscripts and books, 2018)
"The nine contributions in The Trade in Papers Marked with non-Latin Characters initiated by Anne Regourd (ed.) approach global history through the paper trade. They cover, in addition to a paper used in 14th C Persia, papers used in Africa (Ethiopia, Nigeria, Tunisia) and Asia (the Ottoman Levant, Mecca, Persia, Russia, and Yemen) during the 19th-20th C. Primarily based on paper examination and quantitative data, the book invites us to treat papers as a source, and provides tools to determine the production of manuscripts in space and time for the area of interest. This methodology offers new insights on the competition between suppliers to the various markets particularly in respect of the emergence of import-export trading companies"--